The Effect Of Profitability And Liquidity On The Value Of CompaniesIn The Health Sector Listed On The Indonesia Stock Exchange (Idx) - rizza nahdiatul ilmi; m mustaqim (Universitas Kadiri, 2026)
This study was conducted in the context of fluctuating company values and the growth ofthe healthcare sector on the Indonesia Stock Exchange, which are not always in line withincreases in company profitability and liquidity. This situation highlights the gap betweencompanies' financial performance and investor perceptions in the capital market,necessitating an analysis of the factors influencing company value. This study aims toanalyze the effect of profitability, as measured by return on assets (ROA), and liquidity,as measured by the current ratio (CR), on company value, as measured by price to bookvalue (PBV), in healthcare companies listed on the Indonesia Stock Exchange (IDX)during the 2023-2024 period. This study employed a causal quantitative approach with apurposive sampling method, resulting in a sample of 28 companies (56 observations).Data analysis was performed using panel data regression using EViews 13 software,using the common effects model (CEM). The results show that ROA has a positive andsignificant effect on PBV, while CR has no significant effect on PBV. Conversely, ROAand CR simultaneously have a significant effect on PBV.Keywords: Profitability, Liquidity, Company Value, Health Sector